Efektivitas Kebijakan Hukum Pidana tentang Perlindungan Saksi dalam Proses Peradilan - Fachrodin, Fachrodin (Ali Muchasan, 2019)
In Law No 13 Year 2006 About Protection of Eyewitness and Victim that eyewitness who is under the aegis of LPSK is eyewitness in doing an injustice case. Although is not expressed is expressly expressed eyewitness in position whose protected, but in program the eyewitness protection in various eyewitness state protected by eyewitness giving boldness assist the Prosecutor, and is not eyewitness from defendant party. Target in this research is: (1) to analyze the formula’s punishing the eyewitness protection in course of criminal justice. (2) To analyze the execution of protection policy punish for eyewitness in course of criminal justice. (3) For describe of policy formula’s punish about eyewitness protection in course of criminal justice in the future. This research is inclusive of research with the approach of yuridis normative. Data type in this research is data secondary. Technique data collecting by using technique of bibliography study. Technique data processing by editing, interpretation, and systematization. Data from direct first source analyzed by trying to look for the clarification comprehensively to activity that happened in eyewitness protection in course of jurisdiction. Conclusion result of this research is: (1) Formula’s punish the eyewitness protection in course of criminal justice represent the phenomenon procedure of criminal Indonesia, where about in straightening of will always touch with all enforcer punish the itself. Protection human right for eyewitness and victim very majored, so that process criminal justice formed by Law of Protection of Eyewitness and Victim. (2) protection Policy punish for eyewitness in course of criminal justice very needed, especially which is all victim or eyewitness in course of criminal justice which during the time feel do not get the protection by law, and even once in a while there is eyewitness in crime case which finally is oppositely; also made suspect. With the Number Law 13 Year 2006 about Protection of Eyewitness and society Victim put the big expectation, especially hardness case in domestic, hardness to child, corruption case, collision of human right and other rights collision case which is under the aegis of this law. (3) Policy formula’s punish about eyewitness protection in course of criminal justice in the future, representing a aspiration in system punish the national touching all people and nonalignment. In order to reaching this end needed harmonious punish to be existed by union punish in a system punish, so that water down the society comprehend and execute the law. Thereby existed by sense justice of society which obedient always and meekly at law.